2017
DOI: 10.1111/hae.13271
|View full text |Cite
|
Sign up to set email alerts
|

Let's Talk Period! Preliminary results of an online bleeding awareness knowledge translation project and bleeding assessment tool promoted on social media

Abstract: An online screening tool is an effective method of identifying individuals concerned with abnormal bleeding. A significant portion of the general population report experiencing symptoms of abnormal bleeding. In women, the most frequently reported bleeding symptoms were menorrhagia and postpartum haemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 15 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…It is likely that bleeding symptoms in men are more of a red flag to both clinicians and patients than in women, leading to faster presentation and diagnosis. It is suggested that 15% of women with heavy menstrual bleeding have an underlying inherited bleeding disorder, most commonly VWD, but remain undiagnosed, given barriers such as lack of understanding regarding the difference between normal and abnormal bleeding and social stigma . Menorrhagia was one of the most predictive symptoms of VWD in all regression models, highlighting the importance of screening women with unexplained menorrhagia for underlying bleeding disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that bleeding symptoms in men are more of a red flag to both clinicians and patients than in women, leading to faster presentation and diagnosis. It is suggested that 15% of women with heavy menstrual bleeding have an underlying inherited bleeding disorder, most commonly VWD, but remain undiagnosed, given barriers such as lack of understanding regarding the difference between normal and abnormal bleeding and social stigma . Menorrhagia was one of the most predictive symptoms of VWD in all regression models, highlighting the importance of screening women with unexplained menorrhagia for underlying bleeding disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The women would appreciate it if their gynaecologists and haematologists could involve them in decision‐making regarding type of surgery and complication rate. Reynen et al showed that the use of an online website could be an effective method to increase awareness of a bleeding disorder when women are faced with HMB.…”
Section: Discussionmentioning
confidence: 99%
“…Women should be given professional guidance to websites that are useful and accurate (EC), such as pamphlets from the American College of Obstetricians and Gynecologists (ACOG) 23 at acog.org/patient‐resources/faqs or misforwomen.com 24 ●Social media platforms have been shown to increase awareness of undiagnosed bleeding disorders 17 . Women could be directed to social media groups or platforms that might increase their awareness (EC). ●Telephone or video chat counseling of patients has been demonstrated to increase patient satisfaction, lower anxiety score, and not alter treatment complication or outcomes 12 .…”
Section: Resultsmentioning
confidence: 99%
“…24 • Social media platforms have been shown to increase awareness of undiagnosed bleeding disorders. 17 Women could be directed to social media groups or platforms that might increase their awareness (EC).…”
Section: Counseling On Aub In Telemedicinementioning
confidence: 99%